Blood, breath, fears redux, and panic attacks comment on Roth, Wilhelm, and Pettit (2005). [article]. - Ley, R.
This article discusses the hyperventilation theory (HVT) of panic attacks (PAs) proposed by R. Ley in the context of criticisms raised by W. T. Roth, F. H. Wilhelm, and D. Pettit. Their interpretation of HVT is flawed by misunderstanding, misinterpretation, and oversimplification of the complex psychophysiological principles on which current HVT is based. Consequently, the "propositions" they derive are inappropriate. Further, Roth et al. disregarded/overlooked: (a) differences among types of PAs, (b) abundant empirical evidence that PA patients are distinguished by presence or absence of prominent respiratory symptoms (e.g., overbreathing), and (c) Ley's (1992b) classification of PAs based on 10 psychophysiological distinctions. The review by Roth et al. falls short of standards required to falsify HVT. Current HVT of PAs is tenable and testable. -- (from the author)
Keywords: hyperventilation; Panic attacks; Respiratory alkalosis